(untitled) (Journal of Pedagogical Inventions and Practices, 2022)
In this article, some short stories characterized by the category of stylistic devices are considered by stylistic analyses. Futhermore, the article consists of pieces taken from different English literary texts. As regards stylistic devices are hold peculiar features of fictional texts. Stylistic devices can always provide emotionality on any particular texts.